The Influence of Taxpayer Understanding, Perception of Fairness, Ease of Tax Payment, and Taxpayer Compliance on The Optimization of Regional Revenue from The Opsen Scheme of Motor Vehicle Tax and Vehicle Ownership Transfer Fee - Dhafin Muhammad Akbar; Mita Yesica Octavia; Hidayatullah (Universitas Teknologi Yogyakarta, 2025)
The implementation of Law Number 1 of 2022 concerning Financial Relations between the Central Government and Regional Governments (UU HKPD) introduces a surtax mechanism for Motor Vehicle Tax (PKB) and Vehicle Ownership Transfer Fee (BBNKB) as an effort to strengthen regional fiscal capacity. This issue is important to research because the success of the surtax is one indicator of regional fiscal independence. Previous research has heavily emphasized taxpayer compliance as the main determinant of revenue optimization but has not comprehensively explored the role of administrative ease and perception of fairness. The research problem of this study is how taxpayer understanding, perception of fairness, and ease of tax payment influence taxpayer compliance and the optimization of regional revenue through the PKB-BBNKB surtax scheme. This study uses a quantitative approach with a five-point Likert scale questionnaire distributed to taxpayers in DKI Jakarta Province who have paid PKB or BBNKB in the last two years (purposive sampling). Data were analyzed using SmartPLS 4 through validity, reliability, and structural model testing. The results show that taxpayer compliance does not have a significant effect on revenue optimization and does not act as a mediator. The novelty of this study lies in the identification of administrative ease and perception of fairness as direct determinants of revenue optimization. The research recommendations are to improve fiscal transparency, develop digital services, and enhance public communication strategies. Future research is recommended to expand the research focus to other provinces and use a longitudinal method to observe long-term dynamics.